2022
DOI: 10.1177/00938548221098976
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being in Frontline Correctional Officers: A Mixed-Method Systematic Review

Abstract: Correctional officers (COs) work in high-stress environments, frequently experience critical incidents and have shown high levels of burnout. The current review synthesizes and evaluates literature on determinants of CO well-being. The review followed the Joanna Briggs Institute approach for mixed-method systematic reviews. Eligible studies measured subjective or psychological well-being in frontline COs. Studies of disorder absence or nonfrontline COs or associated professions were excluded. Searches of psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 73 publications
0
11
1
Order By: Relevance
“…Moreover, these COs, mentor and client alike, can strategize and discuss ways of overcoming hardship, and coping with the demands of their job, which can help to enhance resilient attributes. In a recent systematic review by O. Miller et al (2022), it was found that when officers had supportive figures in their lives, they were better able to devise effective coping mechanisms, such as detaching from the job, that helped in preventing the onset of emotional consequences following trauma exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these COs, mentor and client alike, can strategize and discuss ways of overcoming hardship, and coping with the demands of their job, which can help to enhance resilient attributes. In a recent systematic review by O. Miller et al (2022), it was found that when officers had supportive figures in their lives, they were better able to devise effective coping mechanisms, such as detaching from the job, that helped in preventing the onset of emotional consequences following trauma exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review by O. Miller et al (2022), it was found that when officers had supportive figures in their lives, they were better able to devise effective coping mechanisms, such as detaching from the job, that helped in preventing the onset of emotional consequences following trauma exposure. This finding once again aligns with the theoretical principle raised earlier that people, and certain people in particular for COs, can be instrumental in helping officers deal with the tribulations of their job.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…It is likely that observed increases in stress specific to worries about public stigma and negativity toward professionals in the legal system might compound with additional workplace stressors (Evers et al, 2020; Walters, 2022), further taxing these individuals and contributing to mental health problems. What is more, staff in juvenile prison settings who have higher levels of stress and greater difficulty coping are more likely to have reduced well‐being (Miller et al, 2022), thus modeling inappropriate behavior to the young people in the prisons and creating strain in their relationships (Schaufeli & Peeters, 2000; Taylor & Swartz, 2021). Increased stress also contributes to correctional staff turnaround (Harney & Lerman, 2021), which results in less stability in care for young people.…”
Section: Understanding and Participating In Social Movementsmentioning
confidence: 99%
“…Much of the recent scholarship has addressed the workplace experiences of correctional officers, including job satisfaction, job stress, organizational commitment, turnover intent, and burnout (Butler et al, 2019; Lambert et al, 2021). Others have examined the real and perceived dangers of working in a correctional institution as well as officers’ physical, mental, and emotional well-being (Miller et al, 2022; Regehr et al, 2021). Beyond important work in the United Kingdom (e.g., Crewe, 2009; Liebling et al, 2012), comparatively less attention has been devoted to how officers supervise people who are incarcerated.…”
Section: Introductionmentioning
confidence: 99%